Effects of soil water deficit on leaf nitrogen, chlorophylls and spad chlorphyll meter reading on growth stages of soybean - Ahmed, Shakil Uddin (Bangladesh Journal of Botany, 2012)
Soybean leaf Nitrogen (N) status correlated linearly with the amount of chlorophylls and SCMR at flowering stage in response to water deficit levels. In addition, SCMR showed significant positive correlation with chlorophylls at flowering stage. Grain yield significantly correlated to the leaf nitrogen as well as to the chlorophylls and SCMR at flowering stage in response to water deficit levels. These relationships indicated that the water stress decreased leaf nitrogen, chlorophylls and SCMR which in turn caused decreased grain yield of soybean. The results from the study suggest that, flowering stage is the best time for prediction on the adverse effects of water stress on leaf nitrogen assimilation, chlorophylls and SCMR on potential yielding ability of soybean. Key words: Soil water deficit; Leaf nitrogen; Chlorophyll (a+b); Growth stages; Soybean DOI: http://dx.doi.org/10.3329/bjb.v40i2.9773 Bangladesh J. Bot. 40(2): 171-175, 2011 (December)